An analytical model for temperature and crystalline evolution analysis of carbon fiber reinforced polymer composites during cooling. Issue 10 (13th July 2020) - Fang, Haidong; Gu, Junfeng; Li, Zheng; Ruan, Shilun; Shen, Changyu
Abstract: An analytical model for analyzing the temperature and crystalline evolution of short carbon fiber reinforced polymer composites during cooling was established, and the model was firstly verified by calculating the crystallization kinetics of a short carbon fiber reinforced polypropylene (SCFRPP) plate during isothermal and nonisothermal crystallization. Then the model was extended to calculate the temperature and crystalline evolution of two numerical examples of SCFRPP parts during cooling with different temperature boundaries, and the effects of cooling rate and short carbon fiber (SCF) content were analyzed and compared. According to the results, SCF increases the onset crystallization temperature and accelerates the crystallization rate due to the formation of transcrystal. During the cooling stage, SCF changes the evolution of crystalline and temperature complicatedly, and the changes are more significant under lower cooling rate. Abstract :